'Time to Ranch it Up!': Ethics and satire in new media. (September 2020) - Romanowski, Max; Sheldon, Zachary
YouTube and Internet culture have changed expressions of comedy, especially on television. Some forms of TV entertainment content emphasise shock value, resulting in a satirical strain of comedy that stresses absurdity. Such a trend may be observed in The Eric Andre Show (2012–) and Nathan for You (2013–2017), two US comedy TV series which satirise an Internet style of filmmaking while simultaneously critiquing the culture that created it. This article examines these shows for how extreme methods support or detract from their perceived effect, and whether or not such satirical tactics are valid as a way of bringing about change.